(untitled) - Dr Saira Batool (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Syed Jamaluddin Afghani and Allama Iqbal can rightly be credited as being the unparalleled great philosophers of modern Islamic ideology and advocates of the unity of Muslim Ummah. Through their enlightened thoughts and teachings, they not only analyzed the shortcomings of the Muslim rulers, scholars and political leaders but also provided a manifest roadmap for the renaissance of the Islamic world, besides suggesting a solution for excluding ideological slavery and the exploitative despotic political and imperialistic hegemony imposed on the Islamic world by Western powers and the enemies of Islam. In the backdrop of historical events especially the struggle of the brave Afghan nation against two great superpowers of the USSR and the USA in the past, as well as the huge political, economic and survival challenges faced by the current regime of Taliban in Afghanistan, this article attempts to establish the striking relevance and the much-needed compliance with the great teachings of the revolutionary and visionary sages and reformers of the Islamic Ummah, Jamaluddin Afghani and Allama Iqbal.